Study of Carbon Fiber Layout Orientation Effect on Joining with Aluminium - BIN AZMAN, MUHAMMAD; KATIMON, MOHD NIZAM (Research Progress in Mechanical and Manufacturing Engineering, 2024)
This study seeks to investigate how different orientations of carbon fibre specifically set at 45°, 70°, 135° impact the strength and durability of aluminium joints when bound together using epoxy resin. Understanding the relationship between the positioning of carbon fibre and the effectiveness of joining aluminium parts is crucial for optimizing structural integrity. As carbon fibre becomes increasingly integrated into aluminium structures across various industries (Zhang, 2023), determining the most effective orientation for epoxy resin bonding is pivotal in enhancing the reliability of these joints and minimizing material wastage. The methodology involves adhering to the ASTM D5868 a lap shear tensile test standard, systematically arranging aluminium samples with varying carbon fibre orientations, and bonding them using epoxy resin. Three types of orientation set at 45°, 70°, 135° named as type A, type B and type C respectively. Initial insights suggest notable variations in the strength and behaviours of epoxy resin-bonded aluminium joints based on specific carbon fibre layout orientations. By studying stress and strain properties, it shows that in term of stress, type C has the highest value followed by type A and B. For Strain, type B has the highest value followed by type C and A.